Influence of Cutting Position with IBA Hormone for Different Dipping Times on Rooting of Cassia tree Cassia surattensis Burm. Stem Cuttings - Habib, Amal Abdul .S.; Attiya , Hatim J. (Iraqi Journal of Science, 2022)
The present study was carried out in the experimental in the nursery at Al – Dorah (Baghdad). During spring 2015 under natural environmental conditions in plastic house to evaluated the effect of different concentrations of IBA (100, 300, 500, 700 and 1000( mg/1 on different cutting position (basal, sub terminal and terminal) for different dipping times (24, 48) hours, on Cassia surattensis Burm. stem cuttings rooting. After 2 months of planting the results demonstrated that the basal cutting treated with 1000 mg/l IBA in 48 hours dipping time showed the earlier rooted period (4) weeks compared with control treatment 8 weeks. The same treatment also gave the highest mean rooting numbers 1.56per cutting and the highest mean rooting lengths 2.88 cm compared with other treatments. The 1000 mg/l IBA treatment with basal and sub terminal gave the highest mean value of rooting percentage 55.5% in both dipping times compared with control treatment that gave 0.0%.